2009
DOI: 10.3171/2009.2.spine08723
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for cervical interbody grafting

Abstract: Object The objective of this systematic review was to use evidence-based medicine to determine the efficacy of interbody graft techniques. Methods The National Library of Medicine and Cochrane Database were queried using MeSH headings and keywords relevant to cervical interbody grafting. Abstracts were reviewed and studies that met the inclusion criteria were selected. The guidelines group assembled an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 46 publications
0
14
0
2
Order By: Relevance
“…36 Currently, it is unclear from the literature if these osteoconductive carriers result in fusions rates equivalent to autograft . [37][38][39] Recombinant bone morphogenetic proteins have been used as an additive osteoinductive agent to promote fusion. 40,41 There are, however, reports of adverse effects of their use in the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…36 Currently, it is unclear from the literature if these osteoconductive carriers result in fusions rates equivalent to autograft . [37][38][39] Recombinant bone morphogenetic proteins have been used as an additive osteoinductive agent to promote fusion. 40,41 There are, however, reports of adverse effects of their use in the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…However, their use comes with potential problems, including risk of infections and graft rejection, higher rates of collapse and nonunion, especially in multilevel fusions, and prolonged period required for graft incorporation [46]. Ryken et al in a comprehensive review concluded that there appears to be equivalency regarding the use of harvested autogenous bone graft, allograft, polyetheretherketone, and titanium cages in anterior fusion [53]. …”
Section: Treatment Outcomes For Cervical Spondylotic Myelopathymentioning
confidence: 99%
“…The iliac crest has long been recognized among many spine surgeons as a reliable source for cancellous bone. 1,8,13 However, the iliac crest is not an ideal donor site, because a variety of donorsite morbidities can result from its use. 2,7,12,[15][16][17] This has led to the search for other autologous donor sites.…”
Section: Discussionmentioning
confidence: 99%